Scaling Relationship Between the Wavelength of Longitudinal Ridges and the Thickness of Long Runout Landslides on the Moon. Issue 10 (20th October 2021) - Magnarini, G.; Mitchell, T. M.; Grindrod, P. M.; Schmitt, H. H.; Petro, N. E.
Abstract: The formation mechanism of longitudinal ridges in long runout landslides has been proposed to require ice and/or clay minerals, as low friction materials would allow the spreading of the deposit, causing the development of longitudinal ridges by tensile deformation of the slide. The necessity of ice in the formation of longitudinal ridges has been challenged by the finding that the wavelength of longitudinal ridges is 2–3 times the thickness of the deposit in both ice‐free laboratory experiments on rapid granular flows and in a martian and terrestrial long runout landslide, suggesting a scale‐ and environment‐independent mechanism. We conduct morphometric analysis of the longitudinal ridges in two landslides on the Moon, considered ice‐free throughout its geological history: the Tsiolkovskiy crater landslide, and the Light Mantle avalanche in Taurus‐Littrow Valley. We show that Tsiolkovskiy crater landslide exhibits a scaling relationship between the wavelength of its longitudinal ridges and the thickness of its deposit that is consistent with previous studies, supporting the idea that ice is not a necessary condition for the development of longitudinal ridges. As the Tsiolkovskiy crater landslide is laterally confined, it demonstrates that neither the development of longitudinal ridges nor the occurrence of the scaling relationship between the wavelength of the ridges and the thickness of the deposit depend on the lateral spreading of the deposit. Finally, we use the Light Mantle to test the use of the scaling relationship as a tool to estimate the thickness of the deposit when classical geomorphological methods are not applicable. Plain Language Summary: The origin of a pattern of ridges that extend in the direction of motion (called longitudinal ridges) seen in hypermobile landslides is debated. One hypothesis suggests that the pattern derives from landslides spreading over low friction surfaces, such as ice or clay minerals. However, other studies disagree on the necessity of ice and suggest an environment‐independent mechanism, showing that the distance between ridge crests scales with the thickness of the deposit in both ice‐free laboratory simulations, and martian and terrestrial slides. In this study, we measure the distance between the ridge crests and calculated the thickness of the Tsiolkovskiy crater landslide on the Moon, in a region where extensive ice cover is excluded through its history. We find a scaling relationship consistent with previous studies, which supports the hypothesis that ice is not necessary to form longitudinal ridges. As the Tsiolkovskiy crater landslide is laterally confined, we conclude that the lateral spreading is also not necessary to form longitudinal ridges but it does affect the thickness of landslides and the distance between the ridges. We use the Apollo 17 Light Mantle avalanche to test the application of the scaling relationship to infer landslide thickness by measuring the distance between ridges. Key Points: Wavelength of longitudinal ridges and thickness of lunar landslides scale in agreement with laboratory, martian, and terrestrial results The formation of longitudinal ridges does not depend on the presence of ice nor on the lateral spreading of the slide during emplacement The wavelength of longitudinal ridges can be used to estimate the thickness of landslides when other methods are not applicable